Князь Александр Ярославович и король Даниил Романович как люди Средневековья - Мусин, А.Е. (Княжа доба: історія і культура, 2015)
Запропоновано порівняльний аналіз доль
двох чільних постатей історії Східної Європи XIII ст. – князя Олександра Ярославовича
(Невського) і короля Данила Романовича, а
також уявлень сучасників про їх посмертну
долю і святість. Дослідження засноване на базових категоріях середньовічної культури,
що забезпечує від модернізації історії. Запропоновано висновок про штучність протиставлення цих володарів у сучасній свідомості. У житті князів простежуються численні паралелі, які пояснюють не літературні
топоси, а умови середньовічного життя і
менталітету. Існуючі відмінності стосуються, здебільшого, церковної політики та
релігійної культури й продиктовані відмінним політико-географічним розташуванням
їх князівств на карті Європи. Пропонується уточнення початкового періоду історії
Холмської єпархії та ролі єпископа Іоана у
складенні літописного образу Данила Романовича. Канонізація князя Олександра пояснюється існуванням сильного й стабільного
осередку церковної влади поряд з місцем його
поховання у Владимирі, відсутньої у Холмі, де поховано короля Данила. The article provides a comparative study
of the activity of the two key persons in the history
of Eastern Europe in 13th century – Alexander
Jaroslavovych (Nevsky) and king Daniel
Romanovych, and the contemporary perceptions
concerning their sainthood and afterlife veneration.
The study is based on the categories of
the medieval culture that allows avoiding any
modernization of the history. The conclusion has
been done about the artificial character of opposition of the rulers in the modern mentality. In
the lives of princes many parallels can be traced, which should be explain by similar conditions
of medieval life and mentality, not by literary topos. The differences relate primarily to their
church politics and religious culture, caused by different positions of two principalities on
the political map of Europe. The article revises the initial period of the history of the diocese of
Chełm and the role of Bishop John in the formation of the image of the King Daniel in the Galician-
Volhynian Chronicle. The canonization of
the Prince Alexander should be explained by the existence of a well established church organization
near his shrine in Vladimir, which was absent in Chełm where Daniel had been buried.